PRELIMINARY PHYTOCHEMICAL SCREENING AND IN VITRO ANTI-MICROBIAL ACTIVITY OF ETHANOLIC EXTRACTS OF FRUITS OF ANNONA RETICULATA AGAINST STANDARD PATHOGENIC STRAINS - Paul, Sujata; Dash, Biswajit; Bora, Aditya Jyoti; Gupta, Bikash (International Journal of Current Pharmaceutical Research, 2018)
Objective: To evaluate the anti-microbial activity of ethanolic extract of fruits of Annona reticulata (family-Annonaceae) in conjugation with phytochemical analysis. Methods: The ethanolic extract of fruits of Annona reticulata (family-Annonaceae) was prepared by Soxhlet extraction and analysed for phytochemical constituents using standard methods. The anti-microbial activity of the plant extract was examined against bacterial strains and fungal strains using disc diffusion method. Results: The present investigation shows the phytochemical analysis, anti-microbial activity of the ethanolic extract of the plant Annona reticulata. Various phytochemical analyses revealed the presence of alkaloids, saponin, flavonoids, carbohydrates, glycosides, steroids, proteins and amino acids and tannins. The anti-microbial activity of the ethanolic extract of the plant showed significant result against all the of the test organisms. Conclusion: The present study concluded that ethanolic extract of fruits of the Annona reticulata contain high presence of phytochemicals. The ethanolic extract of the plant was found to possess promising anti-microbial activity when compared with the standards.